Prevalence and determinants of workplace violence among nurses in public tertiary hospitals in Enugu state, Nigeria - Nwanneka Chidinma Ghasi; Daniel Chukwuemeka Ogbuabor (PLoS ONE, 2026)
Background Despite its impact on nurses’ well-being, hospital efficiency, and patients’ quality of care, published studies on workplace violence against nurses in sub-Saharan Africa are scarce. This study assessed the prevalence, characteristics, and determinants of workplace violence among nurses in public tertiary hospitals in Enugu State, Nigeria. Methods The study was a cross-sectional survey among nurses in the four (4) public tertiary hospitals (n = 450) in Enugu State Nigeria. The nurses were selected from the hospitals using proportional stratified random sampling technique. Data were collected using a self-administered, workplace violence questionnaire for nurses. The outcome variable was nurses’ experiences of workplace violence in the past 12 months, scoring as yes or no. Workplace violence included verbal, physical, and sexual violence. Additionally, we collected socio-demographic and organizational characteristics of the nurses. Nurses’ socio-demographic factors, organizational characteristics and prevalence of workplace violence were summarized using descriptive statistics. We identified the predictors of workplace violence using bivariate analysis and binary regression. The significance level for all inferential analyses was p-value less than 0.05. Results Overall, the prevalence of any workplace violence was 92.4%. The prevalence of verbal violence, physical violence, and sexual violence are 91.1%, 13.3%, and 2.0% correspondingly. Relatives of patients perpetrated most workplace violence among nurses in this study. Female nurses were more likely to experience verbal abuse than male nurses (COR = 2.84, 95%CI: 1.09–7.42, p = 0.002). Being a registered nurse (AOR = 2.06, 95%CI: 1.13–3.78, p = 0.019), direct contact with patients (AOR = 21.04, 95%CI: 3.17–139.82, p = 0.002), working in accident and emergency units (AOR = 6.91, 95%CI: 2.82–16.93, p < 0.001) increased the likelihood of physical violence against nurses. Direct contact with patients (AOR = 20.71, 95%CI: 3.54–121.12, p = 0.001) increased the likelihood of sexual violence. Conclusion Workplace violence among nurses in public hospitals need to improve. Decision-makers and practitioners can incorporate these findings into safeguarding policies and strategies to improve nurses’ safety and monitor interventions to eliminate workplace violence against nurses in Nigeria.